2004
DOI: 10.2337/diabetes.53.12.3074
|View full text |Cite
|
Sign up to set email alerts
|

The α2–5′AMP-Activated Protein Kinase Is a Site 2 Glycogen Synthase Kinase in Skeletal Muscle and Is Responsive to Glucose Loading

Abstract: The 5AMP-activated protein kinase (AMPK) is a potential antidiabetic drug target. Here we show that the pharmacological activation of AMPK by 5-aminoimidazole-1-␤-4-carboxamide ribofuranoside (AICAR) leads to inactivation of glycogen synthase (GS) and phosphorylation of GS at Ser 7 (site 2). In muscle of mice with targeted deletion of the ␣2-AMPK gene, phosphorylation of GS site 2 was decreased under basal conditions and unchanged by AICAR treatment. In contrast, in ␣1-AMPK knockout mice, the response to AICAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
163
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(192 citation statements)
references
References 40 publications
25
163
2
2
Order By: Relevance
“…2). This is in agreement with a previous study, which reported that GS phosphorylation at sites 3a and 2 is decreased in rested rat muscle with low glycogen levels (39,40). Altogether our results indicate that GS FIGURE 3.…”
Section: Discussionsupporting
confidence: 83%
“…2). This is in agreement with a previous study, which reported that GS phosphorylation at sites 3a and 2 is decreased in rested rat muscle with low glycogen levels (39,40). Altogether our results indicate that GS FIGURE 3.…”
Section: Discussionsupporting
confidence: 83%
“…Glycogen is a proposed regulator of GS activity [30] and GS phosphorylation at sites 2+2a [28]. Consistent with this, the exercise-associated decrease in muscle glycogen content has been shown to be a factor involved in GS activation [30][31][32].…”
Section: Discussionmentioning
confidence: 70%
“…Glycogen synthase kinase 3 (GSK3) and AMP-activated protein kinase (AMPK) are major upstream regulators of GS [27,28]. Insulin stimulation inhibited GSK-3β activity by increasing Ser9 phosphorylation on both experimental days ( p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The CBM in the AMPK-b subunit causes the complex to associate with glycogen particles in intact cells (Hudson et al 2003;Polekhina et al 2003), and AMPK also associates with the surface of glycogen particles in vivo (Bendayan et al 2009). The function of this association remains uncertain, although AMPK does phosphorylate two proteins that are targeted to glycogen, that is (1) muscle glycogen synthase (mGS), whose phosphorylation at site 2 causes inactivation Jorgensen et al 2004), and (2) R5/PTG, which targets the catalytic subunit of protein phosphatase-1 (PP1) to glycogen (Vernia et al 2009). Phosphorylation of R5 is proposed to promote its ubiquitylation and degradation, so that phosphorylation of mGS and R5 by AMPK would not only cause inactivation of mGS, but also dissociation from glycogen of the protein phosphatase (PP1) that reactivates it, the two effects cooperating to inhibit glycogen synthesis.…”
Section: Mammalian Ampk-structure and Regulationmentioning
confidence: 99%